Cephalometric evaluation of soft tissue changes following bilateral sagittal split setback osteotomy. Issue 2 (May 2015) - Nair, K.S. Ravindran; Kumar, Ajith; C. Ramakrishnan, Sobhana; Ramachandran, Bindu; Devi, Manisha
Abstract : Introduction: The analysis of facial soft tissue and associated esthetic outcome is the most challenging and unsatisfactory component in the global orthognathic treatment plan. Soft tissue profile changes are basically dictated by skeletal movements that can be compared by cephalometric ratios. Objective: To compare the presurgical and postsurgical soft tissue profile and to correlate the movement of the soft tissue envelope with that of the hard tissue. Study design: This was a cross-sectional study carried out at the Department of Oral and Maxillofacial Surgery, Government Dental College, Trivandrum, Kerala, India after approval from the institutional ethical committee (IEC/C/12-A/2011/dated 20-12-2011). Materials and methods: Lateral cephalograms of 10 patients who had undergone BSSO set back were analyzed and compared at 3 and 6 months, respectively, with the preoperative lateral cephalograms using the paired t -test. Results: On an average, retropositioning of osseous pogonion was followed by soft tissue pogonion by 88.8%, soft tissue menton by 99.8%, labrale superius by 39.8%, and inferior labra by 63.6% in the sagittal plane. There was also a significant percent change in the vertical plane, except for the labrale superius. Conclusion: It has been found that the soft tissue pogonion change is more evident and predictable than soft tissue menton with reference to hard tissue. Significant vertical changes were observed in relation to most of the parameters, except labrale superius. Some of the ratios correlating the hard and soft tissue found were concordant with those found in the literature.